MODEL ARSITEKTUR POHON KAWASAN JALUR HIJAU DI KECAMATAN CICALENGKA KABUPATEN BANDUNG - Novia Rosalina (Fakultas Kehutanan Universitas Winaya Mukti, 2019)
The existence of green line is very important for people's lives, because being planted in this area is very useful for reducing urban pollution that is built from vehicles and factories equipped with gas containing solid particles. One of component for green line is tree, because it’s have branching that’s reducing urban pollution. The branching architecture is a morphological representation of a particular phase of a series of tree growth series, real and observable at all times. The object of research is a tree census was carried out on Jl. National II / Jl. Bypass of the Cicalengka green line area then describe of model architecture. The method of research by sensus for numbering species of tree and identify of tree architecture model using book by F. Halle & R.A.A. Oldeman, namely: An Essay on The Architecture and Dynamics of Growth of Tropical Trees. The results of reseach are 946 trees that grow on Jl. Nasional III in the Cicalengka green line area. There are 15 tree species found 4 tree architectural models namely troll, rauh, aubreville, and champagnat.